Screening, Identification, and Fermentation Characteristics of Lactic Acid Bacteria from Pickled Potherb Mustard and Potential Applications - Xiaoxue Kong; Jiaxin Zhang; Hui Shen; Nan Shi; Hui Zhou; Yi Li; Yuxing Guo; Haibo Luo; Lijuan Yu (Foods)
We identified strains of lactic acid bacteria from fermented potherb mustard that showed excellent fermentation properties. The goal was to identify superior starter cultures that would optimize the traditional fermentation process, reduce fermentation duration, and improve the quality of pickled potherb mustard. Four strains were screened: Weissella cibaria (LAB1, LAB3) and Leuconostoc mesenteroides (LAB2, LAB4). Then, after in vitro tests of tolerance to low pH and salt levels as well as lactic acid production ability, nitrite degradation ability, antibacterial properties, and antioxidant activity, LAB1 and LAB2 were selected as the best strains. Next, these two strains were used as starter cultures for fermenting potherb mustard. Each was inoculated into the fermentation solution. Compared to natural fermentation, both showed beneficial effects, including reducing nitrite content, shortening fermentation time, maintaining the reducing sugar, and increasing the levels of nitrogenous amino acids. Microbial diversity analyses revealed that, prior to fermentation, the predominant microbial communities were Methylobacterium and Sphingomonas, which primarily originated from the surrounding environment. However, 30 days after inoculation with the two strains, there was a significant increase in the abundance of Weissella and Lactobacillus, and Weissella emerged as the dominant bacterium. Inoculation of LAB1 effectively stabilized the bacterial community of the potherb mustard and significantly enhanced the content of nitrogenous amino acids in the final product, indicating that it is highly suitable as a mono-starter. On the other hand, LAB2 led to reduced nitrite content and facilitated the proliferation of Weissella and Lactobacillus, indicating that it is an effective mixed starter. Due to its limited effect on acid production, it is not recommended as a mono-starter for pickled mustard production.